Dendritic Platinum–Copper Alloy Nanoparticles as Theranostic Agents for Multimodal Imaging and Combined Chemophotothermal Therapy. (6th June 2016) - Zhou, Zhengjie; Hu, Kewen; Ma, Rui; Yan, Yang; Ni, Bing; Zhang, Yunjiao; Wen, Longping; Zhang, Qiang; Cheng, Yiyun
Abstract : Theranostic nanoparticles that possess multiple diagnostic modalities and allow spatiotemporally controlled therapies can significantly improve therapeutic outcomes and reduce adverse effects. Here, an intelligent and biocompatible theranostic formulation is developed based on dendritic platinum–copper alloy nanoparticles (DPCN) for cancer therapy. DPCN have excellent photothermal effect, and can load anticancer drugs such as doxorubicin in their porous structure and release the loaded drugs in response to near infrared light or moderate acidic stimulus. They also inherently have multimodal imaging modalities. Upon the guidance of photoacoustic imaging, DPCN‐mediated photothermal treatment efficiently inhibits tumor growth in vivo. Furthermore, doxorubicin‐loaded DPCN completely suppress the tumor growth even under a low treatment temperature, which avoids hypothermia‐induced damage to normal tissues. Our study develops an excellent theranostic nanoparticle with inherent multimodal imaging and therapeutic modalities for chemophotothermal cancer therapy. Abstract : Dendritic platinum–copper alloy nanoparticles (DPCN) are developed as an excellent theranostic agent . DPCN inherently possess multimodal imaging modalities, photothermal effect, and drug loading capability. Upon the guidance of photoacoustic imaging, DPCN‐mediated chemophotothermal treatment efficiently inhibits the tumor growth in vivo.